(untitled) (SAARC Journal of Agriculture, 2021)
Allelopathy is expected to be an important mechanism in the plant invasion process. The experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh to evaluate the effect of aqueous extract of mustard crop residues on weed management and crop performance of wheat. The experiment consisted of three cultivars of wheat viz., BARI Gom 19, BARI Gom 21, BARI Gom 24 and five levels of aqueous extract such as no crop residues (C0), mustard crop residues: chaffed leaves soaked in water in 1:20 ratio (w/v) (C1), 1:30 ratio (w/v) (C2), 1:40 ratio (w/v) (C3), hand weeding (C4). The maximum weed growth was noticed with the cultivar BARI Gom 19 and the minimum was found in the cultivar BARI Gom 21. The grain yield as well as the other yield contributing characters produced by BARI Gom 21was the highest among the studied varieties. The highest percent inhibition of all weed species was caused by hand weeding. The highest numbers of tillers hill-1, numbers of grains spike-1, 1000 grain weight, grain yield and straw yield were observed where hand weeding is done and followed by the application of aqueous extract in 1:20 ratio (w/v). BARI Gom 21 cultivar with all treatments produced the highest grain and straw yield among the treatment combination. The results indicate that different amount of aqueous extract of mustard crop residues showed potential activity to suppress weed growth and it has a significant effect on the yield of wheat. Therefore, mustard crop residues might be used as an alternative way for weed management in effective and sustainable crop production. SAARC J. Agri., 18(2): 17-26 (2020)